Systemic inequality, sustainability and COVID-19 - Aladuwaka, Seela; Wejnert, Barbara; Alagan, Ram, 1962- (Research in political sociology, 2022)
Systemic Inequality, Sustainability and COVID-19provides an opportunity to engage in a critical dialog on the consequences and interactions of COVID-19 with social inequalities and environment management.